THE ROLE OF CELEBRITY ATTRACTIVENESS AND CREDIBILITY IN INFLUENCING IMPULSIVE BUYING TENDENCY FOR UNIQLO - Mona, Cynthia Vanessa; Utama, Louis (International Journal of Application on Economics and Business, 2025)
The aim of this study is to examine the influence of celebrity attractiveness and celebrity credibility on impulsive buying tendency, as well as to test purchase intention as a mediator between celebrity attractiveness, celebrity credibility, and impulsive buying tendency. The sample used in this study consists of 311 respondents who have purchased Uniqlo products. Data were collected through an online questionnaire distributed via Google Forms using a non-probability sampling technique. The collected data were then processed using PLS-SEM with the assistance of SmartPLS 3 software. The results of this study indicate that: Here’s a more fluent paraphrase of your statement:(a) The attractiveness of a celebrity positively influences impulsive buying tendencies. (b) The attractiveness of a celebrity positively impacts purchase intention. (c) A celebrity’s credibility has a positive effect on impulsive buying tendencies. (d) A celebrity’s credibility positively influences purchase intention. (e) Purchase intention has a positive impact on impulsive buying tendencies. (f) Purchase intention acts as a mediator in the relationship between celebrity attractiveness and impulsive buying tendencies. (g) Purchase intention mediates the effect of celebrity credibility on impulsive buying tendencies.